PERMAINAN BOLA BASKET MODIFIKASI TERHADAP INTERAKSI SOSIAL ANAK AUTIS DI SEKOLAH LUAR BIASA - AINI ALHUDA, QURROTU (Jurnal Pendidikan Khusus, 2017)
Abstract : From the observation in SLB Sinar Harapan Probolinggo, there are 6 children with autism who have barriers in social interaction. So, children need to be given special treatment that can increase social interaction. The treatment is a basketball modification, the goal for which children are able to interact well and know the influence of basketball modification. This research uses quantitative approach and type of pre experimental design with one group pre test - post test design. Statistical techniques in the analysis of this research data is a sign test. Data collection techniques in the form of observation and documentation. Research subjects used as many as six children with autism. The results showed that the value of Z arithmetic (Zh)=2.04 greater than the value of crisis Z table (Zt) 5%=1.96 (Zh> Zt), then Ho is rejected Ha accepted, so there is influence between the basketball modifications to the social interactions of children with autism.   Keywords: Basketball Modification, Social Interaction